금속연료-피복재 상호확산 방지를 위한 크롬 도금법 적용 연구 - 김준환; Jun Hwan Kim; 이강수; Kang Soo Lee; 양성우; Seong Woo Yang; 이병운; Byoung Oon Lee; 이찬복; Chan Bock Lee (대한금속·재료학회지, 49(12), 2011)
Studies have been carried out in order to reduce fuel-cladding chemical interaction (FCCI) behavior of metallic fuel in sodium-cooled fast reactors (SFR) using an electroplating technique. A 20㎛thick Cr layer has been plated by the electrochemical method in the Sargent bath over the HT9 (12Cr-1Mo) clad material and diffusion couple tests of the U-10Zr metallic fuel as well as the rare earth alloy (70Ce-29La) have been conducted. The results show that the Cr plating can prevent FCCI behavior along the fuel-clad interface. However, cracks developed through the thickness during plating, which resulted in the migration of some fuel constituents. Variation of bath temperature, application of pulse current, and post heat treatment have been conducted to control such cracks. We found out that some conditions like the pulse current and the post heat treatment enhanced the layer property by reducing the internal cracks and improving the diffusion couple test.